Antineutrophil cytoplasmic antibodies in synovial fluid from patients with rheumatoid arthritis - Puszczewicz, Mariusz (Reumatologia/Rheumatology, 2006)
ANCA presence in rheumatic diseases has been well documented. The frequency and clinical significance of ANCA in patients with rheumatoid arthritis are not well established. The aim of the study was to evaluate the prevalence and specificity of antineutrophil cytoplasmic antibodies in synovial fluid from patients with rheumatoid arthritis. Synovial fluid samples were obtained from 377 patients with rheumatoid arthritis without symptoms of vasculitis. The control group was taken from 183 patients with osteoarthritis. ANCA titers and type were determined by indirect immunofluorescence method (IIF). Antigenic specificity was detected by ELISA method. ANCA were found by IIF in 28.6% of patients with rheumatoid arthritis. Perinuclear pattern of ANCA was observed in 80.5% and atypical ANCA in 19.4% of cases. We did not observe C-ANCA or reactivity against proteinase 3. In 19.6% of synovial fluid samples, ANCA yielded reactivity against myeloperoxidase, in 44.1% against lactoferrin and in 9.8% against lysozyme. 18.6% of cases indicated reactivity against cathepsin G and elastase. IgM-ANCA were detected in 24.5% and IgG ANCA in 75% of cases. In 45% it was IgG1 class and in 35% IgG3. Summary ANCA presence in rheumatic diseases has been well documented. The frequency and clinical significance of ANCA in patients with rheumatoid arthritis are not well established. The aim of the study was to evaluate the prevalence and specificity of antineutrophil cytoplasmic antibodies in synovial fluid from patients with rheumatoid arthritis. Synovial fluid samples were obtained from 377 patients with rheumatoid arthritis without symptoms of vasculitis. The control group was taken from 183 patients with osteoarthritis. ANCA titers and type were determined by indirect immunofluorescence method (IIF). Antigenic specificity was detected by ELISA method. ANCA were found by IIF in 28.6% of patients with rheumatoid arthritis. Perinuclear pattern of ANCA was observed in 80.5% and atypical ANCA in 19.4% of cases. We did not observe C-ANCA or reactivity against proteinase 3. In 19.6% of synovial fluid samples, ANCA yielded reactivity against myeloperoxidase, in 44.1% against lactoferrin and in 9.8% against lysozyme. 18.6% of cases indicated reactivity against cathepsin G and elastase. IgM-ANCA were detected in 24.5% and IgG ANCA in 75% of cases. In 45% it was IgG1 class and in 35% IgG3.